Analisis Pengaruh Penerapan Pengelolaan Kinerja Keuangan Bank Syariah di Indonesia - Indah Lestari; Chuzaimah Batubara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Good corporate governance implementation (transparency), accountability (accountability), responsibility (responsibility), independence ( independence), and fairness. Therefore, this study invertigates the financial performance of Islamic Commercial banks Services Authority (OJK) Islamic Banking Stastics that apply to each bank. Financial performance (Y) and Good Corporate Governance (X) are the variables of this study. The result of the test analysis show that Good Corporate Governance has a positiveÂ  and significant impact on financial performance. Meanwhile, the coefficientof determination (R2) in adjusted R2 is 0.156, indicating that the independent variable of 15.6% is responsible for the financial performance of Islamic Commercial Banks, while other variables have a large influence.